Aanzicht / Uitzicht : Het Museum Kurhaus Kleef - Bachér, Ingrid; De Werd, Guido; Diedenhofen, Wilhelm; Kratz, Paul; Nikkels, Walter; Palmen, Manfred; Thelosen, Karl; MKK (Museum Kurhaus Kleve), Kleve (Nijmegen : SUN, 1997)
Thorn Prikker, Johan ; Mataré, Ewald ; Kollwitz, Kathe ; Sintenis, Renée ; Beuys, Joseph ; Klein, Yves ; Christo ; Penone, Giuseppe ; Boltanski, Christian ; Pistoletto, Michelangelo ; Merz, Mario ; Polke, Sigmar ; Warhol, Andy ; Erben, Ulrich ; Heerich, Erwin ; Uecker, Günther ; Struth, Thomas ; Fritsch, Katharina ; Baumgarten, Lothar ; Schütte, Thomas ; Wall, Jeff ; Gursky, Andreas ; Förg, Gunther ; Kiefer, Anselm
Nederlands
boek